PENINJAUAN ULANG MARGA CITRUS (RUTACEAE) DI KAWASAN MADURA - Arifin Surya Dwipa Irsyam; Tatik Chikmawati (PTTI, 2015)
Flora of Java does not clearly mention Citrus species in Madura. Since it was published in 1965, there are no review on Citrus of Madura. This research was undertaken to provide an updated information on Citrus of Madura. Plant explorations were conducted in Bangkalan, Sampang, Pamekasan and Sumenep districs. a Total of ten species of Citrus were obtained. One of them, C. × floridana (J. Ingram & H. Moore) Mabb., is a new record for Java and Madura.